Percutaneous cryoablation of renal masses: Washington University experience of treating 129 tumours. (13th November 2012) - Kim, Eric H.; Tanagho, Youssef S.; Bhayani, Sam B.; Saad, Nael E.; Benway, Brian M.; Figenshau, R. Sherburne
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? For patients who are unfit for extirpative surgery, percutaneous cryoablation (PCA) presents a minimally‐invasive alternative for the treatment of renal masses. PCA has been demonstrated to be safe, with complication rates <10% being reported consistently. Studies have suggested that a minimal and insignificant decline in renal function can occur after PCA. Finally, among studies with a follow‐up >20 months, treatment success rates range from 75% to 96%. However, longer‐term oncological and functional results for patients treated with PCA are relatively limited. The present study profiles one of the largest reported experiences with PCA for renal masses: 129 tumours in 124 patients. Our complication rate was comparable to that observed in other reported studies. At a mean follow‐up of 30 months, treatment success was achieved in 87% of tumours, which is in line with published PCA success rates. On multivariable analysis, tumour size >3.0 cm was found to be significantly associated with treatment failure. A minimal but statistically significant renal functional decline was observed, with 20% of patients experiencing a progression in National Kidney Foundation‐Chronic Kidney Disease stage. On multivariable analysis, age >70 years, hilar tumour location and postoperative day 1 estimated glomerular filtration rate <60 mL/min/1.73 m2 were found to be significantly associated with renal functional decline. The present study confirms that PCA of renal masses represents a safe alternative to surgery in patients with substantial medical comorbidities. In the present cohort, baseline patient and tumour characteristics probably impact the risk of tumour recurrence, as well as renal disease progression, after PCA. Objective To evaluate perioperative, oncological and functional outcomes after percutaneous cryoablation (PCA) for renal masses based on our single‐centre experience. Patients and Methods We retrospectively identified 124 patients who underwent PCA for 129 renal tumours between March 2005 and June 2011. Patient demographics and baseline clinical characteristics, tumour features, perioperative information, and postoperative outcomes were recorded. Oncological outcomes were defined by radiographic evidence of recurrence on follow‐up computed tomography or magnetic resonance imaging. Renal disease progression was defined by a change in National Kidney Foundation‐Chronic Kidney Disease stage. Results Patients had mean (sd) age of 72.6 (10.2) years; mean (sd) tumour size and nephrometry score were 2.7 (1.1) cm and 6.5 (1.7), respectively. Our overall complication rate was 9% (11/124), whereas the major (greater than Clavien II) complication rate was 2% (2/124). Significant predictors of renal disease progression following PCA included age ≥ 70 years (odds ratio [OR], 4.31, P = 0.03), hilar tumour location (OR, 4.67, P = 0.04), and post operative day 1 estimated glomerular filteration rate ≤60 mL/min/1.73 m2 (OR, 7.09, P = 0.02). Our treatment success rate was 87% (112/129) at a mean (sd) follow‐up of 30.2 (18.8) months. Tumour size ≥3.0 cm was significantly associated with PCA failure (hazard ratio, 3.21, P = 0.03). Conclusion PCA provides a safe and oncologically effective alternative to extirpative surgery for renal masses in patients with significant medical comorbidities.